In vitro interactions of nystatin and micafungin combined with chlorhexidine against Candida albicans isolates - Maede Salehi; Ali Malekzadeh Shafaroudi; Maryam Daryani; Alireza Khalilian; Fatemeh Ahangarkani; Tahere Molania (Mazandaran University of Medical Sciences, 2022)
Background and Purpose: Oral candidiasis has become a growing problem in hospitals worldwide, and the development of antifungal drug resistance in Candida species constitutes a serious concern. This study aimed to evaluate the in vitro efficacy of nystatin, and micafungin with chlorhexidine against fluconazole-resistant and fluconazole-sensitive Candida albicans (C. albicans) isolates.Materials and Methods: In this experimental-laboratory study, a total of 20fluconazole-resistant (n=10) and fluconazole-susceptible (n=10) C. albicans strains were obtained from the reference culture collection of the Invasive Fungi Research Center in Mazandaran University of Medical Sciences, Sari, Iran. In vitro combination of nystatin and micafungin with chlorhexidine was performed using a microdilution checkerboar method based on the Clinical and Laboratory Standards Institute guideline.Results: Micafungin had the highest antifungal activity against C. albicans susceptible and resistant strains, with a Geometric mean of (GM) =0.008µg/ml and GM=0.008µg/ml, followed by nystatin with GM=0.06µg/ml and GM=0.042µg/ml and chlorhexidine with GM=0.25µg/ml and GM=0.165µg/ml against C. albicans resistant and sensitive strains, respectively. The interaction of micafungin and nystatin withchlorhexidine showed a synergistic interaction against most C. albicans strains. Inaddition, no antagonistic interaction was observed between micafungin, nystatin, and chlorhexidine against C. albicans strains.Conclusion: The synergistic interaction of micafungin with chlorhexidine against azoleresistant C. albicans suggests an alternative approach to overcome antifungal drug resistance. However, further studies are needed for in vivo evaluation. Candida albicans, Chlorhexidine, Combination, Fluconazole, Micafungin,Nystatin